2011
DOI: 10.1186/1471-2407-11-78
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression patterns associated with oncogenesis and sarcomatous transdifferentation of cholangiocarcinoma

Abstract: BackgroundThe molecular mechanisms of CC (cholangiocarcinoma) oncogenesis and progression are poorly understood. This study aimed to determine the genome-wide expression of genes related to CC oncogenesis and sarcomatous transdifferentiation.MethodsGenes that were differentially expressed between CC cell lines or tissues and cultured normal biliary epithelial (NBE) cells were identified using DNA microarray technology. Expressions were validated in human CC tissues and cells.ResultsUsing unsupervised hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…Moreover, TWIST nuclear expression was significantly correlated with high N-cadherin expression [41]. More particularly, TWIST1 was highly expressed in poorly differentiated and sarcomatous CCA tissues suggesting a close relationship between EMT-TFs and the appearance of a mesenchymal phenotype [58].…”
mentioning
confidence: 85%
“…Moreover, TWIST nuclear expression was significantly correlated with high N-cadherin expression [41]. More particularly, TWIST1 was highly expressed in poorly differentiated and sarcomatous CCA tissues suggesting a close relationship between EMT-TFs and the appearance of a mesenchymal phenotype [58].…”
mentioning
confidence: 85%
“…Firstly, in CC, KIAA1114 expression was significantly higher in sarcomatoid SCK cells than adenocarcinomatous cell lines, JCK, Cho-CK, and Choi-CK (Figure 2A). A prior study showed that SCK cells not only possessed strong resistance to chemotherapeutic agents, but also expressed elevated levels of genes involved in cancer progression and metastasis as well as EMT-associated markers [23, 24]. As sarcomatoid CCs are known to be more aggressive and have worse prognosis than adenocarcinomatous CCs [24], increased expression of KIAA1114 may contribute to the acquisition of an aggressive phenotype in CC.…”
Section: Resultsmentioning
confidence: 99%
“…Seol et al [7] reported that CC cell lines did not express SPARC and its expression was barely detected in CC patient tissues. In the present study, we confirmed that BTC cell lines express at least much less Sparc than nonmalignant cholangiocytes (MMNK-1).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, high SPARC levels inversely correlate with good prognosis of gastric [10], pancreatic [11] and prostate cancer [12] but are a favorable marker for colorectal [13] and ovarian cancer [14]. Seol et al [7] have reported that CC cells expressed lower SPARC than normal biliary cells. However, the role of this decreased expression in BTC and of its possible correlation with clinical features is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation